The Effectiveness of Module Based on Discovery Learning to Increase Generic Science Skills - Elok Norma Khabibah; Mohammad Masykuri; Maridi Maridi (Journal of Education and Learning (EduLearn), 2017)
Generic skills are the skills which needed to face the future. In this study, the generic skills that discussed are the generic skills on the science field, called generic science skills. The purpose of this study is to determine the effectiveness of module based on discovery learning to increase generic science skills. This study was conducted at one of the State Madrasah Aliyah in Surakarta academic year 2016/2017. The pre test and post test research pattern with treatment and control class groups were used throughout the study. While the treatment group taught by using module based on discovery learning, the control group was taught by a module that commonly used in the school. As the study concluded, using module based on discovery learning in the learning process is effective to increase generic science skills.